2012
DOI: 10.1002/jnr.23061
|View full text |Cite
|
Sign up to set email alerts
|

Naphthazarin has a protective effect on the 1‐methyl‐4‐phenyl‐1,2,3,4‐tetrahydropyridine‐induced Parkinson's disease model

Abstract: "Neurohormesis" refers to a response to a moderate level of stress that enhances the ability of the nervous systems to resist more severe stress that might be lethal or cause dysfunction or disease. Neurohormetic phytochemicals, such as, resveratrol, sulforaphane, curcumin, and catechins, protect neurons against injury and disease. Naphthoquinones, such as, juglone and plumbagin, induce robust hormetic stress responses. However, the possibility that subtoxic dose of 5,8-dihydroxy-1,4-naphthoquinone (naphthazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…In a different study, the plant root extract napthazarin was investigated for its therapeutic potential following MPTP exposure in mice. Napthazarin was found to reduce astrogliosis and microglial activation in addition to ameliorating DA neuron loss (Choi et al, 2012). However, in the same study by Choi et al, napthazarin was not shown to have direct neuroprotective function, suggesting that the reduction of astrogliosis and microglial activation by napthazarin was sufficient to protect against MPTP-induced DA neurotoxicity.…”
Section: Neuroinflammation and Mptp Neurotoxicitymentioning
confidence: 99%
“…In a different study, the plant root extract napthazarin was investigated for its therapeutic potential following MPTP exposure in mice. Napthazarin was found to reduce astrogliosis and microglial activation in addition to ameliorating DA neuron loss (Choi et al, 2012). However, in the same study by Choi et al, napthazarin was not shown to have direct neuroprotective function, suggesting that the reduction of astrogliosis and microglial activation by napthazarin was sufficient to protect against MPTP-induced DA neurotoxicity.…”
Section: Neuroinflammation and Mptp Neurotoxicitymentioning
confidence: 99%
“…Naphthazarin is an important active ingredient, which exhibits extensive pharmacological activities, including antitumor activity, and due to its low toxicity, it has gained considerable attention (9,10). However, to date the anticancer effects of naphthazarin on human colorectal cancer cells have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulated Nrf2 protects the brain against blood-brain barrier breakdown (Alfieri et al, 2011), spinal cord injury (Zhang et al, 2015) and cerebral ischemia (Son et al, 2010). Therefore, Nrf2 may have a protective role in neurodegenerative diseases, including PD (Choi et al, 2012; Cuadrado et al, 2009), AD (Kanninen et al, 2008), and HD (Stack et al, 2010) as well as traumatic brain injury (Yan et al, 2008). Also, in-vivo and in-vitro studies indicated the potent anti-inflammatory and protective effects of PL by inhibiting nitric oxide production, iNOS expression, prostaglandin-E2 production, TNF-α, IL-1β, IL-6, as well as an NF-κB release in mice and RAW 264.7 macrophage cells (Checker et al, 2014; Luo et al, 2010; T.…”
Section: Discussionmentioning
confidence: 99%